The Impacts of Tourism Development and Resource Assessment in Langkawi, Malaysia: Analyses and Expert System Development - Wayakone, Sengdeuane (1999)
The study is concerned with the assessment of the residents', officers' and visitors' perceptions towards current and future impacts of tourism development and its resources in terms of importance and attractiveness. Based on the results of this study, the knowledge was translated into specific rules, which were incorporated into the expert system (ES). The tool chosen to represent the acquired knowledge in the ES was CLIPS. TIRA_EX (Tourism Impact and Resources Assessment Expert) is the name of the ES. It was developed through a combination of interviews with residents, government officers and visitors. All the knowledge information is stored in databases that can be updated and referred to through the ES. The possible role for TIRA_EX is as an intelligent assistant that aids management in analysing problems in tourism development. At the same time, it provides decision-maker with an effective way of examining possible impacts of tourism development and its resources in order to formulate future strategy for sustainable development of tourism, and keeps its impacts at a desired level, especially in Langkawi Island and in Malaysia in general.